1910's witness to history (vol 2.) milestones of the 20th century (1910-1919) (Kuala Lumpur : Movie Channel Sdn. Bhd., 2001)
Documents the political turmoil, horrors of wars, medical breakthroughs, scientific advancements and social upheaval that made this century one of the most critical and turbulent periods in human history. Assembled from the archival vaults of Pathe and the BBC, Witness to History traces the global milestones of our era. Acclaimed documentation, Gary Tarpinian presents a narrative portrait of the events that shook our world and changed our lives forever.